Anteproyecto de reforma al código de la democracia que garantice el principio de igualdad en la designación de autoridades de las juntas parroquiales del Ecuador. - Rosero Rosero, Greis Aracely (2019)
The present research study was intended to make a critical analysis document which allowed to base the preliminary draft of reform to the Code of Democracy and its guarantee to the principle of equality in the designation of authorities of the Parochial Boards of Ecuador ensuring peoples willing. In order to develop this investigation, it was necessary to divide it into three parts. First, the theoretical foundation which describes the main concepts and critical appraisal about the allocation of seats by the Continuous Dividers Formula “D'Hondt Method” and by the system of majority representation. The second called Methodological design and diagnosis, in which different types of research, techniques and instruments were used, which served as the basis for supporting the proposal and they helped diagnose the current situation of the problem. Finally, the proposal in which the preliminary draft of the reform of the Organic Electoral and Political Organizations Law of the Republic of Ecuador was carried out, “Code of Democracy”, and this allowed to establish a new mechanism for choosing authorities of the Parish Boards of Ecuador, it was explained how the proposal helped solve the deficiencies diagnosed. In addition, the validation of the proposal was carried out by experts, who consistently agreed on the need to apply the proposed proposal, ending with the general conclusions and recommendations.